PERANCANGAN ULANG SISTEM SUSPENSI SHOCKBREAKER PADA KENDARAAN BIMANTARA NENGGALA - Wijanarko, Heri; Sugihandoko; Lufti, Aryananta (JURNAL MEKANIKASISTA, 2025)
To support the vehicle’s high operational activity, a redesign of the shock absorber suspension system on the Bimantara Nenggala vehicle is required. The goal is to make the shock absorber stronger and more durable when traversing rough road surfaces. This is because the Bimantara Nenggala vehicle, which is one of the official vehicles used at the Military Academy, has experienced frequent damage to its shock absorbers during use. The redesign was carried out by changing the steel wire diameter from 14 mm to 16 mm. The research results show that by increasing the wire diameter from 14 mm to 16 mm, the solid length of the spring changed from 56 mm to 96 mm. This modification also altered the number of coils from 2.5 to 4.5, and the spring deflection increased from 39.38 mm to 41.48 mm. This design demonstrates that using a 16 mm wire diameter provides better performance compared to a 14 mm wire diameter. Additionally, the resulting deflection and number of coils are improved compared to the original design.